2001
DOI: 10.1002/ijc.1481
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD1a inhibits HGF-induced motility and scattering of cancer cells through suppression of tyrosine phosphorylation of c-Met

Abstract: We previously reported that ganglioside GD1a, which is highly expressed in poorly metastatic FBJ-S1 cells, inhibits the serum-induced motility of FBJ-LL cells and that the metastatic potential of FBJ-LL cells is completely suppressed by enforced GD1a expression (Hyuga et al., Int J Cancer 1999; 83:685-91). We recently discovered that hepatocyte growth factor (HGF) induces FBJ-LL cell motility. In the present study, the HGF-induced motility of FBJ-S1 cells was found to be one-thirtieth that of FBJ-LL cells. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…Several studies have reported that exposure to gangliosides can induce the production of various inflammatory mediators such as cytokines (Blennow et al 1991). Ganglioside GD1a has been reported to suppress FBJ cells growth (Hyuga et al 2001). Our find the GD1a expression and synthase was increased in cocultured cells were increased the inflammatory factors such as TNF-α, p65, and p 50.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have reported that exposure to gangliosides can induce the production of various inflammatory mediators such as cytokines (Blennow et al 1991). Ganglioside GD1a has been reported to suppress FBJ cells growth (Hyuga et al 2001). Our find the GD1a expression and synthase was increased in cocultured cells were increased the inflammatory factors such as TNF-α, p65, and p 50.…”
Section: Discussionsupporting
confidence: 55%
“…Previously, it has been shown that a-series gangliosides act as negative regulators of c-Met. G D1a inhibits HGF-induced motility and scattering of cancer cells through suppression of tyrosine phosphorylation of c-Met (33). G M3 and G M2 form heterodimers that specifically interact with tetraspanin (CD82) in glycosynapses, and such complexes inhibit c-Met activation and integrin cross talk (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…LA5-22 cells showed no indication of metastasis in mice to whose thighs these cells had been administered and which were sacrificed at 4 to 5 weeks to confirm the presence of tumor cells in organs macroand microscopically. M5 cells as a control mock transfectant were found to have metastasized to lung, liver and kidney [2]. GD1a is thus shown to control the metastatic machinery of FBJ cells but the underlying mechanism for this remains to be clarified.…”
Section: Introductionmentioning
confidence: 92%
“…Ganglioside GD1a regulates cell motility, cell adhesiveness to vitronectin, phosporylation of c-Met and metastatic capacity of mouse FBJ cell lines [1][2][3]. Using cells derived from FBJ-virus-induced mouse osteosarcoma, FBJ-S1 cells with no indication of metastasis were found to express gangliosides GM3 and GD1a, whereas FBJ-LL cells, capable of mestasizing to lung and liver subsequent to subcutaneous transplantation of cells to mouse thigh, possessed GM3 and GD1a but the latter in only limited amounts.…”
Section: Introductionmentioning
confidence: 99%